2016
DOI: 10.1371/journal.pgen.1006152
|View full text |Cite
|
Sign up to set email alerts
|

A High Temperature-Dependent Mitochondrial Lipase EXTRA GLUME1 Promotes Floral Phenotypic Robustness against Temperature Fluctuation in Rice (Oryza sativa L.)

Abstract: The sessile plants have evolved diverse intrinsic mechanisms to control their proper development under variable environments. In contrast to plastic vegetative development, reproductive traits like floral identity often show phenotypic robustness against environmental variations. However, it remains obscure about the molecular basis of this phenotypic robustness. In this study, we found that eg1 (extra glume1) mutants of rice (Oryza savita L.) showed floral phenotypic variations in different growth locations r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 89 publications
0
18
0
Order By: Relevance
“…The Arabidopsis homolog DAD1 and DGL-mediated JA biosynthesis regulates floral development (Ishiguro et al, 2001;Hyun et al, 2008). A gy1 allelic mutant extra glume1 (eg1) also exhibits an abnormal number of pistils and an extra glume-like organ in rice (Li et al, 2009;Zhang et al, 2016). The abnormal flower development of the gy1 mutant may cause the reduction of yield-related traits (Supplemental Table 2).…”
Section: Gy1-mediated Ja Biosynthesis Inhibits Mesocotyl and Coleoptimentioning
confidence: 99%
“…The Arabidopsis homolog DAD1 and DGL-mediated JA biosynthesis regulates floral development (Ishiguro et al, 2001;Hyun et al, 2008). A gy1 allelic mutant extra glume1 (eg1) also exhibits an abnormal number of pistils and an extra glume-like organ in rice (Li et al, 2009;Zhang et al, 2016). The abnormal flower development of the gy1 mutant may cause the reduction of yield-related traits (Supplemental Table 2).…”
Section: Gy1-mediated Ja Biosynthesis Inhibits Mesocotyl and Coleoptimentioning
confidence: 99%
“…Heat shock proteins also play an important role in response to thermal stress. Heat treatment greatly increased HSP90 expression, which directly interacted with transport inhibitor response 1 (TIR1) to prevent its degradation and modulate auxin-mediated plant growth [ 37 , 38 ]. It has been reported that HSFs function upstream of HSPs in heat response [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The other reason is non-stomatal restriction. Stress inhibits photosynthesis by affecting the activity of Rubisco and the PSII structure of the photosystem (Zhang et al 2016 ). Chlorophyll content is one of the most widely used physiological indicators because it directly affects the efficiency of photosynthesis (Croft et al 2017 ).…”
Section: Drought Stressmentioning
confidence: 99%
“…The accumulation of some metabolites has a significant contribution to the process of high temperature tolerance. The lipase gene EG1 , localized in the mitochondria and plastids, mediates the mitochondrial lipase pathway under high temperature, regulating lipid metabolism and downstream gene expression (Zhang et al 2016 ). High cytoplasmic levels of Ca 2+ promote heat tolerance in plants.…”
Section: The Influence Of Heat Stress On Ricementioning
confidence: 99%